Why They Don’t Burned? Lessons from Bengkulu Forest Fire Management, Indonesia - Murhaini, Suriansyah (Opción)
Forest fires are one of the major problems for the global environment because they are both causes and consequences of global warming. This problem is increasingly urgent for Indonesia, which is one of the largest countries contributing to forest fires. In the last five years, almost all provinces except the capital city of Jakarta have experienced the forest and land fires. Of all the burnt provinces, Bengkulu was the least affected by the fire, although it was surrounded by the province with the highest intensity of forest and land fires in Indonesia. The purpose of this study is to identify the factors that cause Bengkulu to have a very low intensity of forest and land fires. The method used is a literature study both news, reports, and research results related to forest fires in Indonesia and Bengkulu in 2019. The results show that there are five main factors that contribute to the low level of forest and land fires in Bengkulu: (1) effectiveness of media framing for provincial leadership comprehensive action, (2) local wisdom of tribal communities, (3) wide and evenly distributed conservation areas managed by central and local governments, (4) extensive palm plantation, and (5) international cooperation. The combination of these factors makes Bengkulu have very minimal forest fires. The government is expected to immediately take the perspective of stakeholders that involve local communities, businesses, and the media to assist in the prevention and suppression of forest and land fires in Indonesia. This study is the first research that identifies a unique area as a source of best practice in preventing forest and land fires and explores the factors driving this prevention effort.